The Effect of Environmental Social Governance Disclosure, Investment Opportunity Set, and Profitability on Firm Value - Novita, Nadya; Dharma, Fitra; Syaipudin, Usep (Asian Journal of Applied Business and Management, 2024)
The purpose of this study is to find empirical evidence on whether environmental social governance disclosure, investment opportunity set, and profitability have a positive effect on firm value. The population of this study are companies listed in the ESG Leaders Index and the Sri Kehati Index. This research is a quantitative study using secondary data taken from the company database on the Indonesia Stock Exchange with a total of 78 observational data in the observation period 2020-2023. This research was statistically tested using a multiple linear regression analysis test. The results showed that environmental disclosure, governance disclosure, and profitability have positive effect on firm value. Meanwhile, social disclosure and investment opportunity set have no positive effect on firm value.